(untitled) (Bangladesh Journal of Urology, 2026)
Background: Transurethral Resection of Prostate (TURP) remains gold standard treatment option for BEP. But this procedure has got some expected complications, among them intra-operative and postoperative hematuria has a higher prevalence rate of 3.5-15.7 ℅. So effective strategies and measures should be adopted to ensure better postoperative outcome in TURP patients in terms of reducing peroperative bleeding and its related catastrophes. Short term pre-treatment with finasteride can be an option suited best for TURP in reducing per-operative blood loss & for better postoperative outcome. Methods: This was a hospital based quasi-experimental study conducted in the Department of Urology, Dhaka Medical College hospital, Dhaka in between January, 2021 to December, 2021 with100 patients having enlarged prostate with moderate to severe LUTS aged within 50-80 years & with pre-operative prostate volume between 40-80 grams. The total sample size was divided in two groups. Whereby group A (n=50) had received 2 weeks of finasteride 5 mg once daily tablet and group B (n=50) was treated with vitamin-D3 2000 IU daily dose as a placebo prior to TURP. All of them underwent Trans-urethral Resection of Prostate. Post-operative follow up was designed as early post-operative follow up and follow up after 28 days of TURP. Results: The baseline variables were comparable among the groups. Statistically significant differences were seen in the time duration of resection which was respectively 43.97±8.79 min and 66.32±18.64 min (p value <0.0001), in group A & B, also a significant difference was found in irrigation fluid during resection (10.50±2.40 in group A versus 19.20±0.54 in group B, p value <0.0001). There was slightly greater postoperative hemoglobin drop in non finasteride group, 10.85±0.5 versus 10.6±0.5gm/dl (p value of < 0.0001). Three patient (6%) from group A and 12 (24%) patients from group B had encountered postoperative hematuria (with a p value of <0.001), 2 patient (4%) and 10 patients (20%) required blood transfusion from group A and B (p value 0.001), 2 patient (4%) and 6 patients (12%) encountered clot retention from group A and B. In the post-operative follow up after 4 weeks, QOL in IPSS were improved in 43 (90%) patient out of 50 in finasteride group, while 34 patient (70%) out of 50 in group B (p value <0.001). In same follow up, the mean ± SD PVR in group A was 15±4.6 ml versus 22±8.3 ml in group B (p value <0.001). Q max on uroflowmetry done on 28th day after TURP, the Mean ± SD 18.2 ± 1.4 ml/sec in group A versus 16.5 ± 4.2 ml/sec in group B (p value 0.0078). Conclusion: Short term pre-treatment with finasteride was found effective to ensure better outcome in TURP by reducing intra-operative & post-operative blood loss along with better maximum flow rate & lesser amount of post voidal residue. Bangladesh J. Urol. 2025; 28(2): 85-92